Differential effects of arachidonic acid and docosahexaenoic acid on cell biology and osteoprotegerin synthesis in osteoblast-like cells - Kruger, Mariana (University of Pretoria, 2013)
Thesis (PhD (Physiology))--University of Pretoria, 2006.